IMPLEMENTASI LITERASI TEKNOLOGI DALAM PEMBELAJARAN GEOGRAFI DI SMA NEGERI 15 PADANG - Khairani Anisya putri; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to describe the implementation of technological literacy in geography learning at SMA Negeri 15 Padang as seen from the indicators of technological literacy skills, namely content, process, context, and attitudes. This type of research is a quantitative descriptive study. The population of this study were students of class X majoring in social studies and MIA at SMA Negeri 15 Padang, totaling 252 students. The technique used in this sampling was simple random sampling, the sample was taken randomly, totaling 72 students. The data source of this research is primary data, namely data obtained from class X students and secondary data, namely data obtained from Administration of SMA Negeri 15 Padang. The research instrument was a questionnaire and the data were processed using a percentage formula. The results showed that the implementation of technological literacy in geography learning at SMA Negeri 15 Padang is in a good category with a score range of 113.6-138.6 and the number of students answered at a percentage of 65%, with details: (1) The content indicator is at good category with a value range of 21.4-25.2 with the number of students answering at a percentage of 68.1%. (2) The process indicator is in the good category with a score range of 28.2-33.6 with the number of students answering at a percentage of 54.2%. (3) The context indicator is in a fairly good category with a score of 14-17 with the number of students answering at a percentage of 51.4%. (4) The attitude indicator is in the good category with a score of 48.6-58.8 with the number of students answering at a percentage of 62.5%.